PENGARUH SUPERVISI AKADEMIK DAN DISIPLIN GURU TERHADAP ETOS KERJA GURU SMK NEGERI SE-LAMPUNG TIMUR - Sukatno, Sukatno; AM, Juhri (Lembaga Penelitian UM Metro, 2017)
The purpose of this research is to analyze: (1) the influence of academic supervision on work teacher’s ethos, (2) the influence of teacher’s discipline toward work teacher’s ethos, and (3) the influence of academic supervision and teacher’s discipline simultaneously toward teacher’s discipline. The population of this study is a public vocational high school teacher in East Lampung totaling 251 with the sample used as much as 71 respondents taken using Slovin formula. The results of the study as follows: (1) There is a positive and significant influence of academic supervision on the working teacher ethos. This can be explained by the regression equation Ŷ.= 44,449 +.0,567X1. It is known that the influence of academic supervision the working teacher ethos is 26,6%, (2) There is positive and significant influence of discipline on teacher working teacher ethos. This can be explained by the regression equation Ŷ = 54,466 +.0,465X2. It is known that the influence of teacher discipline of all working teacher ethos is 16,6%, and (3) There is positive and significant influence of academic supervision and teacher’s discipline collectively working teacher ethos of School teacher. This can be explained by the regression equation Ŷ = 26,443 + 0,468 X1 + 0,297X2. It is known that the influence of academic supervision and teacher disicipline competence simultaneously working teacher ethos is 32,5%. Based on the results of this study indicate that a better academic supervision and teacher discipline contribution to the working teacher ethos.